Spatial U-Pb age distribution in shock-recrystallized zircon – A case study from the Rochechouart impact structure, France. (15th March 2020) - Rasmussen, Cornelia; Stockli, Daniel F.; Erickson, Timmons M.; Schmieder, Martin
Abstract: Age determination of impact structures via the zircon U-Pb system remains challenging and often ambiguous due to highly variable effects of shock metamorphism on U-Pb geochronology. It is, therefore, crucial to link the observed zircon microtextures, including their temperature and pressure conditions associated with their formation, directly to the U-Pb ages preserved. Here, we analyzed three recrystallized zircon grains and one plastically deformed zircon crystal from the medium-sized Rochechouart impact structure in the northwestern Massif Central of France. For the Rochechouart impact structure the impact age (206.92 ± 0.32 Ma [ 40 Ar/ 39 Ar]) as well as the tectono-themal history is well established making this study site ideal to test concepts about U-Pb systematics in shocked zircon and to differentiate between shock-driven age resetting and pre-impact crystallization and metamorphic overprinting. Zircon microstructures were studied using scanning electron imaging, cathodoluminescence imaging, and electron backscatter diffraction (EBSD) mapping. Further, we conducted U-Pb Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA-ICP-MS) depth-profiling analysis, allowing us to interpret the resultant age data in discrete steps with increasing ablation time/depth. The U-Pb depth profiling data demonstrate that plastically strained grains are incompletely reset and preserve rim and interior age domains reflecting typical pre-impact (pre-Variscan and Variscan) regional tectonic ages. Our results also reveal that the granular crystals encountered contain microstructural evidence for "former reidite in granular neoblastic" (FRIGN) zircon, reflecting both high-pressure (⩾30 GPa) and high-temperature (⩾1200 °C) conditions. This signifies that FRIGN zircon is now known from an additional, medium sized, impact structure further supporting the hypothesis that this impact induced microstructure is commonly preserved. In addition, FRIGN zircon has a high potential to preserve completely impact-reset crystal domains (∼204 to 207 Ma) that can be identified by our combined analytical approach of U-Pb depth profiling and EBSD mapping, and thus are suitable for determining reliable impact ages.